2007
DOI: 10.1111/j.1464-5491.2007.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of cystatin C and commonly used creatinine‐based methods for detecting moderate and mild chronic kidney disease in diabetes

Abstract: This study suggests that the clinical and biochemical parameters associated with serum cystatin C levels are closely linked to those associated with GFR and highlights the potential usefulness of screening for moderate or mild CKD in subjects with diabetes by simply measuring serum cystatin C levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
3
40
0
1
Order By: Relevance
“…In a recent comparison of rates of decline of GFR in type 1 diabetes at our centre, serial estimates of GFR decline by creatinine-based methods in patients with an initial isotopically measured GFR of 106±2.6 ml min −1 1.73 m −2 underestimated the GFR gradient measured isotopically by over 50% during a follow-up of 10 years [73]. In contrast, we and others have shown that cystatin Cbased methods for estimating GFR accurately reflect reference GFR measurements in the normal to high range [73][74][75][76].…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 58%
“…In a recent comparison of rates of decline of GFR in type 1 diabetes at our centre, serial estimates of GFR decline by creatinine-based methods in patients with an initial isotopically measured GFR of 106±2.6 ml min −1 1.73 m −2 underestimated the GFR gradient measured isotopically by over 50% during a follow-up of 10 years [73]. In contrast, we and others have shown that cystatin Cbased methods for estimating GFR accurately reflect reference GFR measurements in the normal to high range [73][74][75][76].…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 58%
“…In this study, the GFR was estimated by a cystatin C-based formula (cC-GFR), previously shown as an accurate way of evaluating renal function in patients with diabetes (15,16) …”
mentioning
confidence: 99%
“…Преимущество циста-тина С перед креатинином сыворотки для расчета СКФ доказано у пациентов с ДН [36]. По данным многоцентровых исследова-ний, показана клиническая значимость этого маркера для ранней диагностики НФП, прогнозирования риска ССЗ [37]. Кроме то-го, уровень цистатина С может отражать и метаболический ста-тус.…”
Section: терапевтический архив 1 2015unclassified